Optimasi Jumlah Karbopol 1,5%, Triethanolamine, dan Air terhadap Sifat Fisik Emulgel Astaxanthin dan Ekstrak Wortel - Kadek Adinda Suryadewi S.P. (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Skin damage can adversely affect a person's health and physical appearance. One of the factors causing is exposure to free radicals that can trigger various skin problems such as premature aging, hyperpigmentation, to skin cancer. The combination of astaxanthin and carrot extract (Daucus carota L.) can be a natural approach that is promising for skin care because it contains antioxidant carotenoids. Astaxanthin and carrot extract are formulated in the form of emulgel preparations to optimize their effectiveness when used on the surface of the skin. The success of an emulgel preparation is not only determined by its active ingredient, but also by the physical characteristics of the preparation. This study aims to determine the optimum formulation of the combination of carbopol 940, triethanolamine, and aquadest in making emulgel preparations with active substances Astaxanthin and carrot extract in order to obtain physical properties that meet the standards. Optimization is carried out using the D-Optimal Mixture Design method through the Design Expert® software version 13.0.0. The evaluated parameters include pH, viscosity, scattering power, and adhesion. This study produced an optimum formulation of emulgel with a composition of 940 1.5% carbopol as much as 40.697 grams, TEA as much as 0.5 grams, and aquadest amounted to 15,188 grams. This formula shows a pH of 5,783 ± 0.0249, viscosity 24,856.7 ± 2,829.61 cps, 5,113 ± 0.4216 cm spread power, as well as the adhesion of 1,873 ± 0.1641 seconds. Based on the analysis using the D-optimal method, Tea is known as the most influential component of the physical characteristics of the Astaxanthin combination emulgel and carrot extract.